Quantum gravity theory across galactic scales: a comparative ‎study of NGC 3198 and DDO 154 - WONG, Wing To; WONG, Wing-Keung (International Journal of Advanced Astronomy, 2025)
The rotation curves of spiral and dwarf galaxies, such as NGC 3198 and DDO 154, challenge Newtonian dynamics and motivate theories beyond the dark matter paradigm. Building on the ‎success of Quantum Gravity Theory (QGT) in explaining NGC 3198’s dynamics, the ‎researchers apply QGT to the dwarf galaxy DDO 154 and perform a comparative analysis. ‎Using HI data from *The HI Nearby Galaxy Survey*, the researchers calculate ‎gravitational scale-lengths ( ‎‎) and quantum-corrected velocities (‎ ‎) for both ‎galaxies. For NGC 3198 (‎ ‎) and DDO 154 (‎ ‎), QGT reproduces ‎observed rotation curves with residuals < 5 km/s and reduced chi-square values ‎ ‎. This study confirms QGT’s universality across galaxy masses and ‎morphologies, eliminating the need for dark matter in both spiral and dwarf systems‎.